PENGARUH METODE DISKUSI DENGAN MEDIA MIND MAPPING DAN KEMAMPUAN AWAL TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS X DI SMA NEGERI 1 SUNGAI PUA KABUPATEN AGAM - Widia Ningsih; Yulhendri Yulhendri (Jurnal Kajian Pendidikan Ekonomi, 2016)
The aims of this research was to reveal (1) the difference between economy learning outcomes of the students who were taught by using discussion method withMind Mapping media and those who were taught by using convensional discussion method, (2) the difference economy learning outcomes reviewed by students’ prior knowledge, (3) the interaction between discussiona methodwith mind mapping media and prior knowledge toward economy students learning outcomes. This research is a quasi-experimental study. The population in this study were all students of class X SMA Negeri 1 Sungai Pua school year of 2014/2015. Samples were taken using purposive sampling technique, elected class X4 (control class) and class X7 (experimental class). Early knowledge of data collection techniques done by giving a test at the beginning of learning  while learning outcome data obtained from the results of the test at the end of learning data analysis technique is descriptive analysis, inductive and hypothesis testing using t-test analysis and Anova Two-Way. The result of data analysis showed that: (1) students who are taught by discussion method with  Mind Mapping media had significantly higher results than students taught through the convensional discussion method with Sig. = 0.025 less than the value of α = 0.05 (Sig. < α), (2) learning outcomes the high prior knowledge of students had significantly higher compared to students who had low prior knowledge with Sig. = 0.000, less than the value of α = 0.05 (Sig. < α) and, (3) there was not interaction between discussionmethodwith Mind Mapping media and prior knowledge toward students learning outcomes. with Sig. = 0.618 higher than the value of α = 0.05 (Sig.> α). Based on these results it is suggested to economics teachers to use discussion method with Mind Mapping media to improve student learning outcomes. Keywords: Learning Method, Mind Mapping, Prior Knowledge, Outcomes, Economy